Integration of Paralympic Athletes into Athletics Canada - Howe, P. (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
This paper explores the integration of Paralympic athletes into Athletics Canada. Highlighting the charitable foundation of sport for the disabled as well as the issue of classification, this paper offers insight into the habitus of Paralympic athletics as a key factor influencing this integration process. Integration is conceptualized on a continuum of compliance where true integration is the goal and segregation is frowned upon. Using ethnographic data collected in participant observation roles as an athlete, administrator, and journalist, the paper illuminates the success of the Paralympics in capturing the imagination of the Canadian public. At the same time, the process of integration within Athletics Canada has been less than successful because the achievement of athletes with disabilities is not as valued, by those who administer the sport, as those of their "able" counterparts. To this end the integration process within Athletic Canada appears to be stuck at the uncomfortable point of accommodation, which means that a truly integrated sport system is still a goal to be achieved.